PENERAPAN METODE EARNED VALUE ANALYSIS MENGGUNAKAN SOFTWARE PRIMAVERA PROJECT PLANNER PADA PEMBANGUNAN INSTALASI PENGOLAHAN AIR LIMBAH - Nadila Agnessia; Drajat Indrajaya (LPPM, 2022)
PT Gasd Geosby Indonesia is a company engaged in environmental services and construction. PT Gasd Geosby Indonesia is handling a Wastewater Treatment Plant (IPAL) construction project in Cikarang for an industrial company. The project experienced delays due to several factors supporting activities. Factors that can affect delays include people, materials, costs, and the tools used. Delay cannot be avoided but can be controlled. One form of project control is to calculate the project completion time and the amount of costs that will be incurred until the project is completed. One of the methods used to estimate the time and cost of the project according to the budget according to the work that has been completed is Earned Value Analysis (EVA). The result of data processing using the Primavera application is Estimate At Completion (EAC) in the 4th week of Rp. 185.682.084, the estimated cost is greater than the project planning cost of Rp. Rp. 147.794.994 if the trend of project implementation during the visit did not change until the end of implementation. From the data obtained based on the results of the field visit at week 4, the estimated completion of the project for 43 days or 14 days from the last day of visit was obtained.